Women's experiences of pharmacological and non-pharmacological pain relief methods for labour and childbirth: a qualitative systematic review - Gill Thomson; Claire Feeley; Victoria Hall Moran; Soo Downe; Olufemi T. Oladapo (BMC, 2019)
Abstract Background Many women use pharmacological or non-pharmacological pain relief during childbirth. Evidence from Cochrane reviews shows that effective pain relief is not always associated with high maternal satisfaction scores. However, understanding women's views is important for good quality maternity care provision. We undertook a qualitative evidence synthesis of women's views and experiences of pharmacological (epidural, opioid analgesia) and non-pharmacological (relaxation, massage techniques) pain relief options, to understand what affects women's decisions and choices and to inform guidelines, policy, and practice. Methods We searched seven electronic databases (MEDLINE, CINAHL, PsycINFO, AMED, EMBASE, Global Index Medicus, AJOL), tracked citations and checked references. We used thematic and meta-ethnographic techniques for analysis purposes, and GRADE-CERQual tool to assess confidence in review findings. We developed review findings for each method. We then re-analysed the review findings thematically to highlight similarities and differences in women's accounts of different pain relief methods. Results From 11,782 hits, we screened full 58 papers. Twenty-four studies provided findings for the synthesis: epidural (n = 12), opioids (n = 3), relaxation (n = 8) and massage (n = 4) - all conducted in upper-middle and high-income countries (HMICs). Re-analysis of the review findings produced five key themes. 'Desires for pain relief' illuminates different reasons for using pharmacological or non-pharmacological pain relief. 'Impact on pain' describes varying levels of effectiveness of the methods used. 'Influence and experience of support' highlights women's positive or negative experiences of support from professionals and/or birth companions. 'Influence on focus and capabilities' illustrates that all pain relief methods can facilitate maternal control, but some found non-pharmacological techniques less effective than anticipated, and others reported complications associated with medication use. Finally, 'impact on wellbeing and health' reports that whilst some women were satisfied with their pain relief method, medication was associated with negative self-reprisals, whereas women taught relaxation techniques often continued to use these methods with beneficial outcomes. Conclusion Women report mixed experiences of different pain relief methods. Pharmacological methods can reduce pain but have negative side-effects. Non-pharmacological methods may not reduce labour pain but can facilitate bonding with professionals and birth supporters. Women need information on risks and benefits of all available pain relief methods.